TINDAK PIDANA PERKOSAAN ANAK DIBAWAH UMUR DI KOTA SEMARANG - Nafisah Nafisah; Safik Faozi (Fakultas Hukum Universitas Stikubank, 2021)
Children have rights, both materially and immaterially, as well as the right to protection of honor. The honor of children is a must, especially for girls, if the honor of a child is carried, then the development of the child can be disrupted, because of his unforgettable past. The honor of children who are snatched away by rape makes the writer interested in studying the crime of rape in the city of Semarang. based on the judge's consideration in making a decision against the perpetrators of the crime of raping underage children in the Semarang District Court. This study uses a normative juridical method. The results of the study showed that the judge's basic considerations in deciding the crime of raping minors, the judge considered from three aspects, namely aspects of legal facts, juridical aspects and sociological aspects and considered four things, namely, legal reviews on the basis of legal facts considerations, legal reviews of based on juridical considerations, legal reviews on the basis of sociological considerations and legal reviews on the basis of philosophical considerations, from this study it can be concluded that judges make decisions based on three aspects and 4 things, this is done to achieve justice as stated in the Pancasila ideology of the fifth principle, namely social justice for all Indonesian people. Keywords: the basis of judge's consideration, perpetrators of the crime of raping minors